Does trade liberalization increase child labor in rural Pakistan? A rural perspective - Khanum, Sana; Ul-Haq, Jabbar; Hye, Qazi Muhammad Adnan; Cheema, Ahmed Raza (Edelweiss Applied Science and Technology, 2024)
Trade liberalization has differentiated effects on the regions (i.e., urban and rural). Concerning regional importance, we investigate the association between trade liberalization (TL) and child labor (CL), with special emphasis on rural areas, using micro-level data from 1990-2005 in rural Pakistan. Our estimation approach analyzes geographical differences in the effects of trade policy through province-level exposure to a reduction in import tariffs. We construct provincial panel data for the investigation of the liaison between trade liberalization and child labor in rural Pakistan. The feasible generalized least-squares (FGLS) method is utilized for empirical analysis. Pakistan is related to trade liberalization and the prevalence of child labor in rural areas. In Pakistan, trade liberalization has given rise to child labor in rural regions. It might be the reason that children who are living in rural areas assist their parents with household chores and on-farm. In rural Pakistan, trade liberalization leads to a rise in child labor. Our results hold up well against a range of control variables. The policy implication of the study is that the government should provide free education programs and packages to the poor, especially in rural areas, for the survival of their lives and then parents should send their children to school instead of work.